Nonlinear periodic system with unilateral constraints - Aizicovici, Sergiu; Papageorgiou, Nikolaos S.; Staicu, Vasile (Topological Methods in Nonlinear Analysis, 2019)
We consider a general periodic system driven by a nonlinear, nonhomogeneous differential operator, with a maximal monotone term which is not defined everywhere. Using a topological approach based on Leray-Schauder alternative principle, we show the existence of a periodic solution.